A doubly end-on azido-bridged trinuclear Cu(II) complex: synthesis, spectral and DFT functional studies. (1st March 2011) - Datta, Amitabha; Das, Kuheli; Huang, Wen-Yen; Huang, Jui-Hsien; Liao, Fu-Xing; Hu, Ching-Han
A trinuclear, doubly azido-bridged Cu(II) complex, [Cu1.50(L)(N3)3(CH3OH)]2, (LH = [(CH3)2NCH2CH2N=CHC6H3(OH) (OMe)]), has been synthesised and fully characterised by elemental analyses, IR, UV-Vis, EPR and DFT studies. Its single crystal X-ray structure reveals that adjacent CuII ions are linked by double end-on azido-bridges; thus the full molecule is generated by the site symmetry of a crystallographic two-fold rotation axis.